1997
DOI: 10.1002/(sici)1099-0968(199709)5:3<184::aid-erv203>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The role of general family environment and sexual and physical abuse in the origins of eating disorders

Abstract: This paper reviews the role of childhood family functioning and of sexual and physical abuse in eating disorders. Bearing in mind the huge methodological differences across studies the following tentative conclusions can be reached: there is evidence of more family pathology in eating disorder families than in normal control families. Those with bulimic disorders seem to have poorer family functioning than restrictors. Different eating disorder subgroups show less or comparable levels of family pathology compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 111 publications
1
22
1
4
Order By: Relevance
“…As with prior studies, family and childhood developmental variables demonstrated important relationships with impulsivity (Corstorphine et al, 2007; Schmidt et al, 1997). The presence of externalizing pathology (such as substance abuse disorder or criminality) in a parent showed positive relation to Acting Out and Destructiveness in the adolescents in our sample, suggesting a possible genetic predisposition to impulsivity in this population.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…As with prior studies, family and childhood developmental variables demonstrated important relationships with impulsivity (Corstorphine et al, 2007; Schmidt et al, 1997). The presence of externalizing pathology (such as substance abuse disorder or criminality) in a parent showed positive relation to Acting Out and Destructiveness in the adolescents in our sample, suggesting a possible genetic predisposition to impulsivity in this population.…”
Section: Discussionsupporting
confidence: 67%
“…While childhood trauma appears to be an independent risk factor for later self-destructive, impulsive behavior (Wonderlich, Crosby, & Mitchell, 2001), some researchers have demonstrated that parents with externalizing symptoms may place their children at higher risk for childhood abuse (Verona & Sachs-Ericsson, 2005). Findings from observational studies also suggest that the manifestations of personality disturbances, such as heightened emotionality and impulsivity, in EDs may be moderated by family dysfunction or environments lacking warmth and stability (Steiger & Bruce, 2007; Schmidt, Humfress & Treasure, 1997). …”
mentioning
confidence: 99%
“…Environmental and genetic factors impact the risk of developing an ED. Up to 70% of cases of AN and BN have been estimated to be triggered by an adverse life event, such as abuse 2 5 6. Existing psychiatric conditions7 or substance abuse in the family,8 9 certain personality traits (such as perfectionism and low self-esteem),8–10 and complex sociocultural factors around body image are also risk factors 2 11.…”
Section: Introductionmentioning
confidence: 99%
“…Speci¢cally, research has indicated that a history of violent physical abuse is associated with the development of eating disorders (Rorty & Yager, 1993;Schmidt, Humfress, & Treasure, 1997). The relationship between the experience of sexual abuse and disordered eating patterns=eating disorders has been explored well in the literature (Moyer, 1997;Neumark-Sztainer, Story, Hannan, Beuhring, & Resnick, 2000;Tobin & Gri⁄ng, 1996).…”
mentioning
confidence: 99%